المسالك التجارية بين حاضرة وارجلان وبلاد السودان خلال الفترة(3-9هـ/9-15م) - تيته, محمد (University of Eloued جامعة الوادي, 2022)
تتحرى هذه المقالة إماطة اللثام عن الدور الذي أدته حاضرة وارجلان في التجارة القوافلية العابرة للصحراء خلال القرون الثالث والتاسع الهجري/التاسع والخامس عشر الميلادي. ونظرا للموقع الاستراتيجي الذي امتازت به هذه الحاضرة وللمرافق التي توفرها للتجار الوافدين إليها، أَهَلَهَا بأن تكون ميناء صحراوي مغاربي بامتياز، حيث أبانت المصادر على ما يقرب عشرون مسلكا تجاريا، منها عشرة كاملة نحو بلاد السودان. This article explores the role played by Warghlan in the trans-Saharan caravan trade during the 3rd, 9th/9th and 15th centuries. Owing to the strategic location of this presence and the facilities it provides to the merchants arriving at it, it has been qualified to be a privileged Moroccan Saharan port, where sources have shown nearly 20 commercial routes, 10 of them entirely towards Bilad Sudan's.